Cargill: the importance of transparency in environmental policy - Huchzermeier, Arnd (Henry Stewart Talks, 2017)
This case study explores Cargill’s defence of its palm oil plantation policies. Following accusations of greenwashing and a blatant lack of meaningful sustainability efforts, Cargill aggressively refuted all allegations. Nevertheless negative publicity continued. The case study outlines the importance of transparency and the need for social web activity and effective communication in programmes to improve corporate reputation.